Radio journalism in America telling the news in the golden age and beyond - Cox, Jim 1939- (McFarland, 2013)
"This is a volume of history validating the contributions of radio toward keeping America informed, and surveying radio's diminished effects in the wake of television in the 1950s. The U.S. was dependent on radio as a source of entertainment during the Great Depression and information gained from it during the Second World War had no parallel"--Provided by publisher
"Introduction: Cool stuff and history light -- Hard copies: the origins of American newspapers -- The origins of electronic journalism -- "Millions are out here listening every day!"--Who owns the ether? It belongs to us all -- Censorship: pressures from without, within -- The art of persuasion: everybody has a bias -- Nights of the roundtable: clashes, conflicts courted -- At all hours: news achieves parity, perceptibly prospers -- Journalism's inducement in a rise of local stations -- Intrinsic outcomes a result of radio's reliance on print -- The fanzines: trade issues to perpetuate the industry -- Optical illusions? News fix? boosting aural text with pix -- Magazine of the airwaves: news in a novel format -- When it's time for news, the big hand is on the 24 -- Baubles, bangles, gadgetry: New marvels dispatch news -- Biographical dictionary of radio journalists."
Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1920-2012; Radio journalism / United States / History / 20th century; Geschichte; Journalist; Hörfunk; Journalistik; USA; Biografie